Pengaruh Website Climate Kids sebagai Media Pembelajaran terhadap Kemampuan Literasi Sains Peserta Didik pada Materi Pemanasan Global - Wardani, Anissa; Vitasari, Mudmainah; Berlian, Liska (PendIPA Journal of Science Education, 2025)
The purpose of this study was to determine the effect of the Climate Kids website as a learning medium on the scientific literacy skills of junior high school students on global warming material. This study was conducted at Yappida Islamic Junior High School with a sample of 30 students in each experimental class and control class. This research method used a quasi-experiment with a nonequivalent control group design. This study concluded that the use of the Climate Kids website as a learning medium had an effect on the scientific literacy skills of junior high school students regarding global warming material. The results showed that the learning process had been carried out very well. The Mann-Whitney test was used to test the hypothesis and obtained a Sig. (2-tailed) result of 0.000 (< 0.05), indicating the rejection of H₀ and acceptance of H₁, with the interpretation of a significant effect. The average pretest score of 39.87 increased to 80.47 in the posttest, indicating that the experimental class achieved an N-Gain score of 67.52% with a fairly effective criterion. The significant influence of the Climate Kids website as a learning tool on scientific literacy skills is evident from the effect size test, which yielded a result of 1.219, a high effect criterion. Furthermore, students responded very positively to the use of the Climate Kids website as a learning tool. This indicates that the Climate Kids website has a significant influence on students' scientific literacy skills.